1987
DOI: 10.1073/pnas.84.19.6874
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the murine cytotoxic T-cell membrane glycoprotein Ly-3 (CD8).

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Antibodies to the mouse CD8 molecules (also known as Ly-2,3) have been shown to precipitate from thymocytes three chains of [35][36][37][38] kDa (a), [30][31][32][33][34] In order to explore the functional role of the Ly-2,3 complex, we have undertaken a series of gene transfer experiments and recently shown that the Ly-3 subunit is not required for Ly-2 to efficiently function in class I MHC recognition [lo]. In order to obtain additional information concerning the possible structure-function relationships existing between the Ly-2 and Ly-3 subunits, we have now isolated and expressed by transfection one Ly-3 cosmid clone.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to the mouse CD8 molecules (also known as Ly-2,3) have been shown to precipitate from thymocytes three chains of [35][36][37][38] kDa (a), [30][31][32][33][34] In order to explore the functional role of the Ly-2,3 complex, we have undertaken a series of gene transfer experiments and recently shown that the Ly-3 subunit is not required for Ly-2 to efficiently function in class I MHC recognition [lo]. In order to obtain additional information concerning the possible structure-function relationships existing between the Ly-2 and Ly-3 subunits, we have now isolated and expressed by transfection one Ly-3 cosmid clone.…”
Section: Introductionmentioning
confidence: 99%
“…28). CD8␣-and ␤-chains have two and one N-linked glycosylation sites, respectively, in the Ig-like domains where they share Ͻ20% identity in their amino acid sequences (12)(13)(14)(15)26). The CD8␤ stalk region is 10 -13 aa shorter than the CD8␣ stalk and is highly glycosylated with O-linked carbohydrates.…”
mentioning
confidence: 99%
“…We had shown previously that there were two Ly-3 transcripts of approximately 1-3 kb and 2 3 kb in poly(A)+ RNA from thymus and spleen tissue (in 1:1 and 1:01 abundance, respectively [6]). Furthermore, it was evident that the transcripts of the thymoma ITT( I )75NS (Ly-3-1) diftered in size from those of (C57BL/6X BALB/c) FI thymus and spleen (Ly-3 2) (Fig.…”
mentioning
confidence: 94%
“…1 b). The largest allotypic fragment of Ly-3 {14 kb) specifically hybridizes with the 750 bp EcoRl fragment of RCCT 136 (6) and hence encodes at least the nine Cterminal amino acids of the Ly-3 protein and the 3' untranslated region of the L3 kb Ly-3 transcript {Fig. lb.…”
mentioning
confidence: 99%
See 1 more Smart Citation